AN ANALYSIS OF HEDGING USES IN SKRIPSI-S EMPLOYING QUANTITATIVE AND QUALITATIVE RESEARCH METHOD - Fauzi, Erfan Muhamad (2014)
This study presents an analysis of hedging as one of metadiscourse strategies in research writing setting. This study concerns the analysis of the difference of hedging uses in research report (skripsi-s) employing quantitative and qualitative research method. Particularly, the hedging uses in this study are analyzed in terms of their surface features and their polypragmatic models. In order to analyze the problems of this study, qualitative method, particularly discourse analysis, is used to interpret the text and to examine the feature of language in use. In addition, the effort of quantification was conducted in order to display countable map of the difference of hedging uses in qualitative and quantitative skripsi-s. The data source is from chapter four of some skripsi-s of similar major (study program). They were collected by purposive sampling in order to figure out the contrast of the use of hedging in skripsi-s employing quantitative and qualitative research method. This study has two female undergraduate students with qualitative skripsi-s and two female undergraduate students with quantitative skripsi-s. The collected data were analyzed based on Hyland's and Vartalla's theory of surface features and polypragmatic models of hedging. From overall calculation of surface features of hedging, It can be seen that the quantitative skripsi-s (19.22) have more hedging uses than qualitative ones (12.72). The gap of difference between both groups is 33.8%. Regarding the polypragmatic models of hedging, quantitative skripsi-s tend to have hedging uses more than quantitative skripsi-s do. The percentage of difference is 36.2%. However, there is no reader-oriented hedge found in quantitative skripsi-s although in terms of hedging use frequency quantitative skripsi-s dominate.